2018
DOI: 10.2478/auom-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Some Topological and Algebraic Properties of α-level Subsets’ Topology of a Fuzzy Subset

Abstract: The theory of fuzzy sets, since its foundation, has advanced in a wide range of means and in many fields. One of the areas to which fuzzy set theory has been applied extensively is mathematical programming. Nevertheless, the applications of fuzzy theory can be found in e.g. logic, decision theory, artificial intelligence, computer science, control engineering, expert systems, management science, operations research, robotics, and others. Theoretical improvements have been made in many directions. Nowadays it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…He [20] further evidenced that smooth topologies collection constitutes a complete lattice. Furthermore, Onassanya and Hošková-Mayerová [21] inspected certain features of subsets of α-level as an integral part of a fuzzy subset topology. Likewise, more specialists in the field like Çoker and Demirci [22], in addition to Samanta and Mondal [23,24], have provided definitions to the concept of graduation intuitionistic openness of fuzzy sets based on Šostak's sense [25] according to Atanassov's [26] intuitionistic fuzzy sets.…”
Section: Introductionmentioning
confidence: 99%
“…He [20] further evidenced that smooth topologies collection constitutes a complete lattice. Furthermore, Onassanya and Hošková-Mayerová [21] inspected certain features of subsets of α-level as an integral part of a fuzzy subset topology. Likewise, more specialists in the field like Çoker and Demirci [22], in addition to Samanta and Mondal [23,24], have provided definitions to the concept of graduation intuitionistic openness of fuzzy sets based on Šostak's sense [25] according to Atanassov's [26] intuitionistic fuzzy sets.…”
Section: Introductionmentioning
confidence: 99%
“…Al Tahan et al [21] defined a topology such that the hyperoperation is pseudocontinuous, and showed that there is no relation in general between pseudotopological and strongly pseudotopological hypergroupoids. In addition, Onassanya and Hošková-Mayerová [22] investigated some topological properties of α-level subsets' topology of a fuzzy subset. Moreover, Çoker and Demirci [23], and Samanta and Mondal [24,25] defined intuitionistic gradation of openness (in short IGO) of fuzzy sets inŠostak's sense [26] by using intuitionistic fuzzy sets introduced by Atanassov [27].…”
Section: Introductionmentioning
confidence: 99%
“…Years later, Demirci [4] defined "smooth groups" by using fuzzy functions and fuzzy equalities [5][6][7]. Since then, many researchers have worked in various directions, such as with smooth subgroups and smooth homomorphisms, generalized vague groups, vague rings, vague ideals, fuzzy multi-polygroups, fuzzy multi-H v -ideals, and other fuzzy algebra [8][9][10][11][12][13][14][15][16][17][18][19].Liu [20,21] proposed and obtained fundamental results of fuzzy subrings and fuzzy ideals of a ring. Dixit et al [22] discussed some basic properties of fuzzy rings.…”
mentioning
confidence: 99%